Analisis Perilaku Generasi Digital Native Terhadap Bank Syariah - Ngali, Fatkhul; Purwanto, Purwanto; Fitriyani, Yeni (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2022)
The motive of this take a look at is to decide the elements that impact the goal of the virtual local technology to undertake Islamic banking offerings. Much preceding research have used the Theory of Planned Behaviour (TPB) withinside the adoption of the conduct of Islamic monetary offerings, however there are nonetheless few research withinside the context of the virtual local technology. Meanwhile, the virtual local technology can end up a marketplace phase for Islamic banking as a way to growth marketplace share. The studies pattern turned into 169 respondents from the virtual local technology who stay in Magelang Regency. The studies information turned into gathered on line the usage of the google shape facility. Data evaluation used Structural Equation Modelling primarily based totally on variance. The results show that theoretically, this research can prove that the Theory of Planned Behavior (TPB) is relevant to be used in analyzing the behavior of the digital native generation towards Islamic banks. Partially, this study proves that the variables in the TPB, namely attitudes, subjective norms and perceived behavioral control, were found to have a significant positive influence on the intention of the digital native generation to adopt Islamic banking services. The next finding is that online shopping behavior is able to moderate the relationship between subjective norms and behavioral control variables that are perceived positively, but in memorization a negative relationship to the intention to adopt Islamic banking services.